Análisis de tendencias en la recuperación de suelos empleando vigilancia tecnológica (2022)
Anthropogenic activities have affected limited natural resources, such as the soil, which supports different activities considered essential for humanity. Consequently, soil health is widely studied by academia, especially in the recovery of degraded soils. Thus, this document developed a technological surveillance that will allow the analysis of the available information related to recovery of degraded soils techniques; this will allow to present a general context, the relevant techniques, and studies in the area. Technological surveillance was carried out using Scopus and ESPACENET databases, which regard to the search for scientific articles and patents, respectively. Different bibliometric indicators were evaluated, such as: number of publications, type of publication, patent registration per country, among others. More than 22.800 articles and 380 patents were found that matched the object of the search. These investigations and inventions are mostly related to phytoremediation processes focused on soil contamination by heavy metals issues and developed in China and the United States, this is related to the growth of intensive technification of agroindustry, the mitigation of the degradation of the soil resource by anthropic contamination, and the sustainable development objectives.